Quality and Nutritional Value of Functional Strawberry Marmalade Enriched with Chia Seed (Salvia hispanica L.) - Özbek, Tuğba; Şahin-Yeşilçubuk, Neşe; Demirel, Birsen (Wiley, 2019)
The aim of the study was to develop and characterize marmalade having functional food ingredients such as omega-3 fatty acid, dietary fiber, protein, and antioxidants with the addition of chia seed (Salvia hispanica L.). During the development of marmalade formulations, sweetener type and chia content in the strawberry marmalade were decided by two-step sensory analysis. In the first step, four different formulas were prepared separately by using sorbitol, isomalt, commercial Stevia™ powder, and isomalt together with sorbitol. The control formula was prepared with sucrose (refined commercial sugar). In the first part of the study, sensorial parameters showed good acceptability for sorbitol. Thereafter, in the second step, marmalades were prepared with 2.5% and 5% (by weight) chia seed including sorbitol. According to sensory panels, sorbitol had the highest acceptance level and the chia seed content was chosen to be used as 5% in the formulations. Chia seed and sorbitol addition increased the phenolic content by 15.45% and the dietary fiber content by 168% and decreased the caloric value by 48% compared to the control prepared with sucrose and without chia seed. The final product had 1.5% omega-3 fatty acid and could be declared as “omega-3 source” in the label. The viscosity of chia-added marmalade was found to be slightly higher than the viscosity of control, even though there was no distinct difference between the two samples. The gel-like character was more dominant in chia-added strawberry marmalade compared to the control. The addition of chia at 5% may contribute to the crosslinking without formation of a gel structure.
Keywords: Nutrition. Foods and food supply; Fiber; Bread; TX341-641; PHENOLIC-COMPOUNDS